2004
DOI: 10.1021/jm0310582
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the Vitamin D Nuclear Receptor Liganded with the Vitamin D Side Chain Analogues Calcipotriol and Seocalcitol, Receptor Agonists of Clinical Importance. Insights into a Structural Basis for the Switching of Calcipotriol to a Receptor Antagonist by Further Side Chain Modification

Abstract: The plethora of actions of 1alpha,25(OH)(2)D(3) in various systems suggested wide clinical applications of vitamin D nuclear receptor (VDR) ligands in treatments of inflammation, dermatological indication, osteoporosis, cancers, and autoimmune diseases. More than 3000 vitamin D analogues have been synthesized in order to reduce the calcemic side effects while maintaining the transactivation potency of these ligands. Here, we report the crystal structures of VDR ligand binding domain bound to two vitamin D agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 31 publications
6
95
2
Order By: Relevance
“…Nuclear receptor-coactivator interactions are mediated by LxxLL motifs located in the coactivator protein that interact with the AF-2 region of a nuclear receptor [9,10]. In this study, we screened a (x) 7 LxxLL(x) 7 phage library against VDR in the presence of 1,25 (OH) 2 D 3 or ZK159222, a selective antagonist of VDR-mediated transcription that competes with the natural ligand for binding to VDR [22][23][24]. Our agonist-derived class of LxxLL peptides showed strong sequence conservation across the region N-terminal to the LxxLL box giving the consensus sequence Lx E/H x H/F P L/M/I LxxLL, which was also consistent with the first three residues N-terminal to the DRIP 205 LxxLL motif.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptor-coactivator interactions are mediated by LxxLL motifs located in the coactivator protein that interact with the AF-2 region of a nuclear receptor [9,10]. In this study, we screened a (x) 7 LxxLL(x) 7 phage library against VDR in the presence of 1,25 (OH) 2 D 3 or ZK159222, a selective antagonist of VDR-mediated transcription that competes with the natural ligand for binding to VDR [22][23][24]. Our agonist-derived class of LxxLL peptides showed strong sequence conservation across the region N-terminal to the LxxLL box giving the consensus sequence Lx E/H x H/F P L/M/I LxxLL, which was also consistent with the first three residues N-terminal to the DRIP 205 LxxLL motif.…”
Section: Discussionmentioning
confidence: 99%
“…Crucial to 1,25D-hVDR Transactivation-Based on the hVDR x-ray crystallographic results (5,(25)(26)(27) His-305 and His-397 form hydrogen bonds (H-bonds) with the 25-OH group of 1,25D (28,29) (Fig. 2).…”
Section: Vdw Contacts Made With Helix-3 and Helix-12 Residues Arementioning
confidence: 99%
“…1C, yellow circles). Residues N424, E425, I426, and S427 are unresolved in the 1,25D-VDR x-ray structures [11,12,13,14,15], but when added in an α-helical orientation to the x-ray construct (pdb code: 1DB1), prior to assembly minimization, it was observed that R402 (H11) formed Coulombic interactions with either E425 and S398 or S427 and S398 (see methods; Fig. 1C, pink ribbon in yellow circle).…”
Section: Intramolecular Electrostatic Stabilization Of the C-terminalmentioning
confidence: 99%
“…1B), have shown that agonists occupy the same relative steric space in the VDR LBD, termed the genomic pocket (G-pocket), and stabilize only the closed helix-12 conformation (VDR-c1, Fig. 1C) [11,12,13,14,15]. Analysis of these VDR structures and molecular models with complete AF2-domains, reveal that unlike any other hormonally regulated NR, H12 is held in the closed conformation (c1) by three salt-bridges: 1) K264---E420 2) R154---K413/ R154---L414/ R154---D232 and 3) R402---S427/ S398/ E425 (Fig.…”
Section: Introductionmentioning
confidence: 99%